Participation and Situated Inequality in the Institutions of Children’s Everyday Lives : Development of the Concepts ‘Participation’ and ‘Conflicts’ - Røn-Larsen, Maja; Højholt, Charlotte (International Review of Theoretical Psychologies, 2026)
This article presents the practice research project “Participation and situated inequality in the institutions of children’s everyday lives” and will serve as a foundation for the two subsequent articles. The aim of the present article is to contribute to conceptual clarification and further development of three key theoretical concepts: participation, conflict, and institutional conditions. Based on the project, it is argued, how these concepts are analytically central to understanding the situated dynamics involved in the production of unequal possibilities of participation in children’s everyday lives in and across institutional contexts. The goal is to pave the way for opening the ’black box of inequality’ by analysing situated inequality in relation to social situations and connections in complex everyday life.